The effect of plastic pails on pallet deflection and pressure distribution for stringer class wooden pallets. Issue 7 (6th April 2021) - Alvarez Valverde, Mary Paz; Horvath, Laszlo; Bouldin, John; Shahabi, Farhad
Abstract : There are 513 million new wooden pallets produced every year in the United States, most of which are purposely built for specific applications. Currently, most wooden pallets are designed with the assumption that they will carry a uniformly distributed, flexible load. However, it has been observed by many researchers that most loads carried by pallets are discrete loads where the interactions between packages cause pressure redistribution defined as load bridging. The load bridging phenomenon has been extensively studied for corrugated boxes, and it has been found that the deflection of the pallet is highly dependent on the number, size and type of corrugated boxes and the design of the pallet used. Although pails are an essential packaging solution used to transport smaller amounts of liquids (1–40 L), there is a lack of understanding about the effect of load bridging on unit loads of pails. The objective of this research was to understand the differences in pallet bending and pressure distribution across the top of the pallet when pallets are loaded with plastic pails compared with a flexible airbag. The results revealed that pallets deflect 32%–89% less when loaded with plastic pails. The load predominantly distributes down the bottom perimeter of the pail, indicating that the design of the bottom of the pail could have a major effect on pallet performance. The effect of plastic pails was dependent on pallet design, indicating that the stiffness of a pallet could have a major effect on load bridging experienced by plastic pails. Abstract : When plastic pails are transported on wooden pallets, the interaction between pails creates a phenomenon called load bridging, which can reduce the deflection of the pallet and therefore increase its load capacity. The results of the study revealed that the reduction in deflection could be as much as 89%.